Microstructure evolution and mechanical properties of friction stir processed TiC/7085Al nanocomposites. (16th March 2020) - Zhou, Dongshuai; Wang, Jian; Lu, Yalin; Bai, Zhihao
Abstract: In this paper, homogeneously dispersed TiC nanoparticles and fine-grained composite was successfully achieved by friction stir processing (FSP) of in situ 0.5 wt.% TiC/7085Al nanocomposites with different rotational speed. The effects of the rotational speed on the microstructures and tensile properties were investigated. Experimental results showed that the stir zone (SZ) exhibited equiaxed recrystallized grains with fine size and a high fraction of high-angle grain boundaries (HAGBs) caused by dynamic recrystallization (DRX). Moreover, the tensile strength and elongation of the friction stir processed (FSPed) composite were significantly improved compared with the base composite. With the rotational speed of 1000 rpm, the composite has the smallest grain size and the optimum mechanical properties. The average grain size decreased to 1.61 μ m, the yield strength (YS), ultimate tensile strength (UTS) and elongation reached to 345 MPa, 429 MPa and 17.8%, respectively.